English teacher PPT gamification skills development in Trenggalek - Wiwiet Eva Savitri; Him'mawan Adi Nugroho; Suvi Akhiriyah; Retno Wulan Dari; Eva Rahmawati; Nur Chakim (Universitas Muhammadiyah Magelang, 2022)
Teachers must overcome the challenges of engaging and interactive English instruction. However, interactive and creative learning is usually conducted online via a digital platform. Sadly, not all Indonesian schools have good internet access. In Trenggalek, East Java, English teachers struggle with a similar issue. To overcome this problem, the PKM team trained English MGMP teachers in Trenggalek to make fun and interactive language games using Power Point (PPT). Although PPT is familiar to the teachers, not many of them are competent in using it to create fun activities. Combined offline and online trainings are being held. The PPT gamification training participants said they enjoyed themselves because the information was simple to comprehend and put into practice. In addition for trainee teachers to successfully follow and implement the training materials, PPT gamification training is tailored to their requirements and abilities.